An exploration of MDT views on key factors to consider when determining a service users required level of security. Issue 1 (20th February 2019) - Khan, Zulaikha; Chidambaram, Arun; Thomson, Michaela; Hurst, Courtney
Abstract : Purpose: The purpose of this paper is to identify what key factors multi-disciplinary teams (MDT) deem as most important when making the decision to move service users from one level of security (including low, medium and high secure services) to another. The researchers used the findings from this study to further develop a tool; the assessment for level of security tool (ALS), which aims to structure and streamline this decision-making process. Design/methodology/approach: Data from 18 interviews (MDT staff) were analysed using the Delphi technique (Dalkey and Helmer, 1963 ). This revealed a range of factors discussed when considering service users moves. Participants were asked to rate these factors in accordance with the Delphi which resulted in the removal of certain less important factors based on their scores. The researchers then compared these factors of relevance with a checklist of 16 items previously proposed by a consultant psychiatrist within the trust. This comparison allowed the researchers to highlight any similarities and differences present. Findings: Findings from staff interviews revealed a range of 20 clinical factors perceived as essential to this process including procedural, relational and physical security aspects. However, variations were evident between the MDT priorities (20 items) and the originally proposed list. This emphasised the need for a tool which facilitates a holistic and streamlined approach. Practical implications: The findings from this research have resulted in the development of the ALS tool comprising of 18 key factors. Originality/value: It is envisaged the development of the ALS tool will not only facilitate and structure the decision-making process but also ensure a person-centred approach. This is because the ALS allows for a holistic approach based on an array of factors deemed important to that particular service user. Furthermore, the ALS tool contributes towards the paucity of published structured professional judgement tools needed to make such decisions.